The PASS panel survey after six waves - Mark Trappmann; Jonas Beste; Arne Bethmann; Gerrit Müller (Journal for Labour Market Research, 2013)
The aim of the Panel Study 'Labour Market and Social Security' (PASS) is to provide a database which allows analysing the dynamics of welfare benefits receipt after the introduction of the Unemployment Benefits II in Germany in 2005. This entails the take up and ending of benefits receipt as well as the social situation of households and individuals receiving benefits, their subjective ways of coping with the situation and the contact to institutions providing the basic income support. PASS is set up as a household panel study with a sample of approx. 10,000 households interviewed in each wave. In addition to household interviews with the heads of the households about 15,000 interviews with individual household members aged 15 and older are carried out. This article provides an overview of the first six waves of PASS. It focuses on the survey's main goals, the questionnaire, the sampling and study design, the number of interviews, data access and methodological research on PASS. The article closes by describing the outlook for future developments.
Keywords: 330; IAB-Haushaltspanel; Forschungsansatz; Stichprobenverfahren; Erhebungsmethode; Datenzugang; wissenschaftliche Begleitung; Grundsicherung nach SGB II; soziale Situation; Arbeitslosengeld II-Empfänger; Befragung; private Haushalte; Interview; Fragebogen